2021
DOI: 10.1097/ee9.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational exposures to chemical mixtures on birth weight using Bayesian factor analysis in the Health Outcome and Measures of Environment (HOME) Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Other traditional methods, such as factor analysis and NMF, have also been employed to address research questions around patterns of environmental exposures. 36 38 Additional techniques, such as frequent itemset mining (FIM) or perturbed factor analysis (PFA), have been borrowed from other fields, adapted, or developed for environmental health data. FIM, a data mining technique commonly employed for retail analysis, has been used to isolate chemical combinations (i.e., patterns) based on their prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Other traditional methods, such as factor analysis and NMF, have also been employed to address research questions around patterns of environmental exposures. 36 38 Additional techniques, such as frequent itemset mining (FIM) or perturbed factor analysis (PFA), have been borrowed from other fields, adapted, or developed for environmental health data. FIM, a data mining technique commonly employed for retail analysis, has been used to isolate chemical combinations (i.e., patterns) based on their prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PFOA and PFOS, other long-chained PFAAs, such as perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnDA), and perfluorohexanesulfonic acid (PFHxS), are considered bioaccumulative in humans (Conder et al, 2008;ITRC, 2020). Epidemiological studies have suggested that certain long-chain PFAAs alter lipid levels in children and adolescents , impair the immune system in children , and restrict fetal growth Marks et al, 2019;Zhuang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This may be of particular concern during pregnancy, a vulnerable period during which exposure to endocrine disrupting chemicals may have short- and long-term consequences for the fetus [ 8 10 ]. Indeed, many studies have demonstrated that gestational PFAS exposure is associated with smaller size at birth and higher BMI in childhood and during adolescence [ 11 17 ]. By contrast, impacts of prenatal PFAS exposure on maternal health remain relatively understudied, despite increasing recognition that maternal health in pregnancy predicts future maternal risk of metabolic and cardiovascular disease [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%